Global existence results for functional differential inclusions with delay - Benchohra, M.; Medjadj, I. (Нелінійні коливання, 2014)
Our aim in this work is to study the existence of solutions of a functional differential inclusion with finite delay. We use the Bohnenblust – Karlin fixed point theorem for the existence of solutions.